Traditional healers' knowledge and infection control practices related to HIV in Bukavu City, Democratic Republic of the Congo - Célestin Kyambikwa Bisangamo; Nessrin Ahmed El-Nimr; Patrick Milabyo Kyamusugulwa; Iman Mohamed Helmy Wahdan; Zahira Metwally Gad (BMC, 2024)
Abstract Background Patients with HIV consult traditional healers (THs). These THs can both delay care for people living with HIV (PLHIV) and transmit HIV through poor infection control practices. The main objective of this study was to evaluate knowledge and practices of THs regarding HIV in Bukavu. Methods A cross-sectional study using quantitative approach was carried out among 71 THs in Bukavu City. The collected data included the following topics: personal and socio-demographic characteristics, HIV knowledge, and infection control practices. Descriptive statistics, independent-samples T-test or F-test, and multiple linear regression were used to analyze the data with a p-value < 0.05. Results The THs' mean age was 49.2 ± 11.2 years, and the majority were aged 40 to < 60 years. Males constituted 88.7% of THs with a male-to-female ratio of 7.9. In general, 47.9% of study participants had poor knowledge about HIV/AIDS infection, 45.1% of them had fair knowledge, and only 7.0% had good knowledge. Overall, 43.7% of THs had poor infection control practices, 52.1% of THs had fair practices, and only 4.2% of participants had good practices. Results of multiple linear regression analysis revealed that none of the personal and demographic variables studied were significant predictors of their knowledge about HIV/AIDS (p > 0.05). In terms of practices, two variables were significant predictors of infection control practices: living in Ibanda and receiving training in taking care of HIV/AIDS. Conclusion and recommendations : The study revealed that THs' knowledge about HIV infection was insufficient and that they had poor infection control practices. Formal standardized training on HIV infection should be organized for all THs so that they can always refer their patients to modern, reliable antiretroviral therapy (ART) clinics and reduce the risk of occupational exposure in their practices. Although PPE's assistance for THs is required in terms of protective measures, the province health authority must also oversee infection control procedures at THs' offices.